Deadly connection - Worth, Lenora (Love inspired suspense., 2020)
On her way to question US Marshall Emmett Gage about a DNA match that implicates his relative in a cold case and a recent murder, Officer Belle Montera's attacked. Now she and her K-9 partner must team up with Emmett to find his cousin and the person after Belle.